0635 Effects of Donepezil in Patients with Residual Excessive Sleepiness of Obstructive Sleep Apnea: A Double Blind; Randomized Placebo; Controlled Study. (27th May 2020) - Sousa, K M; Piovezan, R D; e Silva, L; De melo, C; Poyares, D; Tufik, S
Abstract: Introduction: Residual excessive sleepiness (RES) is presented by 6% of obstructive sleep apnea patients despite effective CPAP therapy. Few interventions have been tested for this condition and are focused on daytime stimulants. Recently, cholinergic activity decline was suggested as a potential mechanism in the pathophysiology of RES. This study aimed to investigate the effects of donepezil, an anticholinesterase inhibitor, in patients with RES. Methods: This double-blind, randomized, placebo-controlled crossover study included participants with RES (35-65 years). Neuropsychiatric disorders, alcoholism, smoking, shiftwork, psychoactive drugs, other sleep disorders were exclusion criteria. Participants were assigned to one intervention arm (donepezil 5 mg for 15 days followed by donepezil 10mg for 15 days or placebo in the morning). After a 20-day wash-out, the same procedure was repeated following the crossover design. Somnolence measured by the Epworth sleepiness scale (ESS) and Maintenance of Wakefulness Test (MWT) were the primary endpoints. PSG, cognitive (trail test, continuous performance test) and Beck's depression scale parameters were secondary endpoints. General Linear Models for repeated measures compared interventions responses. Cohen's d measured effect sizes. Adverse events (AEs) were assessed by questionnaire. Results: The study enrolled eight individuals. ESS was lower in the donepezil arm than in the placebo arm (8.9±4.4 vs 15.7±4.1, p<0.05). Effect size for ESS was high (d 1.61). Other endpoints were not different among study arms. Randomization order didn't affect the results. No AEs were reported. Conclusion: Donepezil improved subjective sleepiness in individuals with RES. To our knowledge, this is the first study to report the effects of a cholinergic intervention in patients with RES. Effect size was high for self-reported sleepiness, which may impact on quality of life and risk of disability in people with RES. Agents acting on the cholinergic system are potential targets for treating RES. Support: Acknowledgements Brazilian National Council for Scientific and Technological Development (CNPq) This study is supported by AFIP (Associacao Fundo Incentivo a Pesquisa).